Dynamics of Women’s Rights in South Korea: Family Law, 1957-2005 - Klamwijit, Thanyanan (Thammasat Journal, 2026)
The abolition of the family head system and the amendment of South Korea’s Family Law in 2005 marked a significant victory for feminist groups, which had been pushing for these changes since the 1950s. However, despite these legal changes, patriarchal values within families and negative views toward women still exist in society today. This article looks at the history of women’s rights in South Korea’s Family Law from 1957 to 2005. It aims to examine the development of women’s rights through the revision of family law, using historical research methods and analyzing sources like parliamentary records and newspapers. The study shows that the first major feminist movement in South Korea in the 1950s came about due to modernization and the breakdown of traditional family and social structures that had emerged since the Japanese colonial era in the 1910s. As the women’s rights movement grew, Confucianism, which had been the foundation of Korea’s traditional social system, became a major barrier to changes in family law. The political and economic conditions at different points in history played an important role in the three major amendments to the Family Law. In the early stages, the women’s rights movement was mainly driven by organizations that focused on legal reforms aimed at the conservative government. Over time, the movement spread to the public, becoming a large social force that led to wider support for women’s rights in family law. However, this shift faced strong resistance from conservative groups. In the end, the growing democracy in South Korea allowed the successful reform of the Family Law in 2005, despite ongoing opposition from certain parts of society.